Pelatihan Penyusunan CV ATS-Friendly dan Strategi Pencarian Kerja untuk Meningkatkan Literasi Karier Mahasiswa - Saipul Al Sukri; Sonia Sischa Eka Putri; Asepma Hygi Prihastuti; Zikri Aidilla Syarli; Hijratul Aswad; Kamaruddin Kamaruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
Increasing competition in the digital labor market requires students to master ATS-friendly CV writing, LinkedIn optimization, and effective online job search strategies. This community service program aims to enhance final-year students’ career preparation literacy through an experiential learning-based training conducted via Zoom Meeting. The program involved 85 students from the Management Study Program at Universitas Islam Negeri Sultan Syarif Kasim Riau and the Accounting Study Program at Universitas Persada Bunda Indonesia. The training employed lectures, demonstrations, guided practice, reflection, and mentoring. Evaluation was conducted using pre-test and post-test instruments to measure participants’ understanding of professional CVs, ATS-friendly CVs, LinkedIn, and digital job search strategies, along with a CV checklist assessing structure, completeness, and ATS compatibility. The results show an increase in the mean score from 57.2 to 85.6 with an N-gain value of 0.66 (moderate category). Improvements were also observed in CV quality, particularly in structure and keyword optimization, as well as increased activation and optimization of LinkedIn profiles. These findings indicate that experiential learning is effective in improving students’ digital career literacy and can be further developed through integration with university career center programs.